Control of the sugarcane borers Chilo infuscatellus and Tryporyza nivella by Bactospeine, a microbial pesticide - Irshad , M.; Rahatullah, Rahatullah; Mirza, S. (1982)
Chilo infuscatellus and Tryporyza nivella are the important sugarcane borers of Pakistan and are being controlled mostly by chemicals. Microbial control has not been tried in Pakistan. Therefore, grqnules and wettable powder of Bactospeine were tested against sugarcane borers at Mardan. Its granular formulation gave higher control than wettable powder.